Myocardial CKIP-1 Overexpression Protects from Simulated Microgravity-Induced Cardiac Remodeling - Ling, Shukuan; Li, Yuheng; Zhong, Guohui; Zheng, Yongjun; Xu, Qing; Zhao, Dingsheng; Sun, Weijia; Jin, Xiaoyan; Li, Hongxing; Li, Jianwei; Sun, Huiyuan; Cao, Dengchao; et al. (Frontiers in Physiology, 2018)
Physiological adaptations to microgravity involve alterations in cardiovascular, neuromuscular, and neuroendocrine systems. These adaptations result in cardiac remodeling and orthostatic hypotension. At present, the mechanism of cardiac remodeling induced by microgravity remains to be disclosed. Casein kinase-2 interacting protein-1 (CKIP-1) is an inhibitor of pressure-overload induced cardiac remodeling by down-regulation the phosphorylation of HDAC4. However, the role of CKIP-1 in the cardiac remodeling induced by microgravity is unknown. The purpose of this study was to determine whether CKIP-1 was also involved in the regulation of cardiac remodeling induced by microgravity. We first detected the expression of CKIP-1 in the heart from mice and monkey after simulated microgravity using Q-PCR and western blotting. Then, myocardial specific CKIP-1 transgenic (TG) and wild type mice were hind-suspended (HU) to simulate microgravity. We assessed the heart alterations in morphology and function by histological analysis and echocardiography. Finally, we detected the phosphorylation of HDAC4, AMPK and ERK1/2 in the heart from wild type and CKIP-1 transgenic mice after HU. The results revealed the reduced expression of CKIP-1 in the heart both from mice and monkey after simulated microgravity. Myocardial CKIP-1 overexpression protected from simulated microgravity induced decline of cardiac function and loss of left ventricular mass. Histological analysis demonstrated CKIP-1 TG inhibited the decreases in the size of individual cardiomyocytes of mice after hindlimb unloading. CKIP-1 TG can inhibit the activation of HDAC4 and ERK1/2 and the inactivation of AMPK in heart of mice induced by simulated microgravity. These results demonstrated CKIP-1 was a suppressor of cardiac remodeling induced by simulated microgravity.